Evaluation of equine articular cartilage degeneration after mechanical impact injury using cationic contrast-enhanced computed tomography. Issue 8 (August 2019) - Nelson, B.B.; Mäkelä, J.T.A.; Lawson, T.B.; Patwa, A.N.; Barrett, M.F.; McIlwraith, C.W.; Hurtig, M.B.; Snyder, B.D.; Moorman, V.J.; Grinstaff, M.W.; Goodrich, L.R.; Kawcak, C.E.
Summary: Objective: Cationic agent contrast-enhanced computed tomography (cationic CECT) characterizes articular cartilage ex vivo, however, its capacity to detect post-traumatic injury is unknown. The study objectives were to correlate cationic CECT attenuation with biochemical, mechanical and histological properties of cartilage and morphologic computed tomography (CT) measures of bone, and to determine the ability of cationic CECT to distinguish subtly damaged from normal cartilage in an in vivo equine model. Design: Mechanical impact injury was initiated in equine femoropatellar joints in vivo to establish subtle cartilage degeneration with site-matched controls. Cationic CECT was performed in vivo (clinical) and postmortem (microCT). Articular cartilage was characterized by glycosaminoglycan (GAG) content, biochemical moduli and histological scores. Bone was characterized by volume density (BV/TV) and trabecular number (Tb.N.), thickness (Tb.Th.) and spacing (Tb.Sp.). Results: Cationic CECT attenuation (microCT) of cartilage correlated with GAG ( r = 0.74, P < 0.0001), compressive modulus ( E eq ) ( r = 0.79, P < 0.0001) and safranin-O histological score ( r = −0.66, P < 0.0001) of cartilage, and correlated with BV/TV ( r = 0.37, P = 0.0005), Tb.N. ( r = 0.39, P = 0.0003), Tb.Th. ( r = 0.28, P = 0.0095) and Tb.Sp. ( r = −0.44, P < 0.0001) of bone. Mean [95% CI] cationic CECT attenuation at the impact site (2215 [1987, 2443] Hounsfield Units [HUs]) was lower than site-matched controls (2836 [2490, 3182] HUs, P = 0.036). Clinical cationic CECT attenuation correlated with GAG ( r = 0.23, P = 0.049), E eq ( r = 0.26, P = 0.025) and safranin-O histology score ( r = −0.32, P = 0.0046). Conclusions: Cationic CECT (microCT) reflects articular cartilage properties enabling segregation of subtly degenerated from healthy tissue and also reflects bone morphometric properties on CT. Cationic CECT is capable of characterizing articular cartilage in clinical scanners.